2014
DOI: 10.5301/jbm.5000081
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MCM2 Detection with Stage and Virology of Cervical Cancer

Abstract: The present study shows that HPV-infected cells strongly express MCM2; nevertheless, our data suggests that MCM2 is not a good biomarker when comparing the different clinical stages of cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Our analysis results showed that the expression levels of TYMS , MCM2 , HELLS , and TOP2A in cervical cancer increased and positively correlated with the prognosis of cervical cancer. Previous studies have shown that MCM2 and TOP2A may be markers for screening of precancerous lesions and cervical cancer, whereas others believe that the expression level of MCM2 cannot predict tumor stage and posttreatment response (Amaro Filho et al, 2014; Kuku et al, 2015). And few studies have followed patients, and analyzed their survival and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis results showed that the expression levels of TYMS , MCM2 , HELLS , and TOP2A in cervical cancer increased and positively correlated with the prognosis of cervical cancer. Previous studies have shown that MCM2 and TOP2A may be markers for screening of precancerous lesions and cervical cancer, whereas others believe that the expression level of MCM2 cannot predict tumor stage and posttreatment response (Amaro Filho et al, 2014; Kuku et al, 2015). And few studies have followed patients, and analyzed their survival and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…26 Amaro Filho et al reported an increasing expression of MCM2 in invasive cervical cancers compared to controls, which was due to the correlation between the MCM2 -positive cells and the presence of HPV DNA detected by in situ hybridization. 27 Another study indicates that cervical cancer cells may use excess MCMs as a backup for replicative stress. 28 The level of MCM4 and PCNA was reported to be upregulated by mutant p53, a primary determinant in variety cancers.…”
Section: Discussionmentioning
confidence: 99%
“…35 Amaro Filho et al also reported an increasing expression of MCM2 in invasive CC compared to control, but they suggested that MCM2 is not a good biomarker when comparing the different clinical stages of CC. 36 PCNA acts as a central coordinator of DNA transactions by providing a multivalent interaction surface for factors involved in DNA replication and cell cycle regulation. Owing to its function, PCNA has been widely used as a tumor marker for cancer cell progression and patient prognosis.…”
Section: Discussionmentioning
confidence: 99%